A survey of international clinical teleneuropsychology service provision prior to and in the context of COVID-19. Issue 7 (16th November 2020) - Hammers, Dustin B.; Stolwyk, Renerus; Harder, Lana; Cullum, C. Munro
Abstract: Objective: Despite expansion of telecommunication strategies across health services and data supporting feasibility of videoconference-based neuropsychological assessment, relatively little is known about teleneuropsychology (TeleNP) use in practice. The current COVID-19 pandemic provides an opportunity for greater use of TeleNP and understanding of neuropsychologists' experience with this unique assessment medium. Methods: During the course of a no-cost global webinar related to practical/ethical considerations of TeleNP practice, attendees were invited to engage in a 26-question survey about their TeleNP use and related COVID-19 concerns. TeleNP practices before the COVID-19 pandemic and early on during the global outbreak were queried among survey participants, along with examination of TeleNP intentions following COVID-19. Results: Multiple countries were represented across five continents, with two-thirds of respondents being from the United States. Approximately one-fourth of respondents reported using TeleNP for clinical interview, feedback, and intervention prior to the onset of the COVID-19 pandemic, and approximately one-tenth of individuals used TeleNP for testadministration. Increased use of TeleNP for clinical interview, feedback, and intervention was reported within the first few weeks of the global COVID-19 outbreak, though the use of TeleNP for testing remained relatively unchanged. Most respondents indicated an intention for future use of TeleNP. Conclusions: Our findings suggest the use of TeleNP is increasing, although use of remote TeleNP testing is still developing. Findings also illustrate increasing use of TeleNP in the context of the COVID-19 pandemic and encourage follow-up investigation in future studies to understand the changing practices and rates of TeleNP provision over time.